HAPMAP: a computer program for the linkage analysis of haploids. - C. R. Bronson; C.-S. Chang; T.-H. Tzeng (Fungal Genetics Reports, 1989)
The development of technology for the detection of variations in DNA sequence is permitting the rapid mapping of the genomes of many organisms.